2022
DOI: 10.1093/nar/gkac722
|View full text |Cite
|
Sign up to set email alerts
|

2′-O-Methylation of the second transcribed nucleotide within the mRNA 5′ cap impacts the protein production level in a cell-specific manner and contributes to RNA immune evasion

Abstract: In mammals, m7G-adjacent nucleotides undergo extensive modifications. Ribose of the first or first and second transcribed nucleotides can be subjected to 2′-O-methylation to form cap1 or cap2, respectively. When the first transcribed nucleotide is 2′-O-methylated adenosine, it can be additionally modified to N6,2′-O-dimethyladenosine (m6Am). Recently, the crucial role of cap1 in distinguishing between ‘self’ and ‘non-self’ in mammalian cells during viral infection was revealed. Here, we attempted to understand… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
55
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(55 citation statements)
references
References 59 publications
0
55
0
Order By: Relevance
“…6D). Thus, the precursor ion m/z 305.086 can be predicted as a methylinosine analog with a ribosyl methylation, which commonly locates at the 2’-OH position of ribose (Ayadi et al, 2019; Drazkowska et al, 2022). The synthetic reference 1-methylinosine compound with methylation at the N1 position of the purine base was detected at a similar retention time to the predicted methylinosine analog (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…6D). Thus, the precursor ion m/z 305.086 can be predicted as a methylinosine analog with a ribosyl methylation, which commonly locates at the 2’-OH position of ribose (Ayadi et al, 2019; Drazkowska et al, 2022). The synthetic reference 1-methylinosine compound with methylation at the N1 position of the purine base was detected at a similar retention time to the predicted methylinosine analog (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…6D). Thus, the precursor ion m/z 305.086 can be predicted as a methylinosine analog with a ribosyl Page11 methylation, which commonly locates at the 2'-OH position of ribose (Ayadi et al, 2019;Drazkowska et al, 2022).…”
Section: Prediction Of Methylinosine and Formyluridine Analogs Enrich...mentioning
confidence: 99%
“…32 Interestingly, the trinucleotide-based approach did not require methylation of the m 7 G ribose to prevent reverse incorporation thanks to an additional base pair between adenosine of the trinucleotide primer and thymidine at the −1 position of the template. 31 A few years ago, several trinucleotide cap analogs became commercially available as CleanCap reagents, 33 and a modified variant of a trinucleotide cap, m 2 7,3 ′ -O GpppA m pG (Figure 3B), has been used for the production of the Comirnaty vaccine. 5 Recently, we reevaluated the trinucleotide analogs of m 7 GpppA*pG and expanded this set with m 7 GpppNpG trinucleotides containing nucleobases other than adenosine (C, G, and U).…”
Section: How To Cap Rnamentioning
confidence: 99%
“…In a follow-up study, we showed that tetranucleotide cap analogs m 7 GpppA m pG m pG are also efficient IVT primers (ca. 90% capping using ϕ6.5 promoter) and provide direct access to mRNAs with cap-2 structures . We then applied a similar approach to incorporate noncanonical caps including NAD, FAD, and UDP-sugars …”
Section: How To Cap Rnamentioning
confidence: 99%
See 1 more Smart Citation